2017
DOI: 10.1093/ije/dyx188
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to perchlorate, nitrate and thiocyanate, and prevalence of diabetes mellitus

Abstract: Higher urinary perchlorate levels are associated with an increased prevalence of diabetes mellitus, independent of traditional risk factors. Future prospective studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…There are some papers which investigate into the possible relationship between perchlorate exposure and other health disruptions. Liu et al [136] suggested linking the increased risk of type 2 diabetes with increased exposure to perchlorate and other goitrogens. Formed upon data obtained from NHANES 2001-2014, 11,443 people were tested for perchlorate levels and then obtained data were correlated with prevalence of diabetes in studied group.…”
Section: Other Potential Perchlorate Exposure Health Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some papers which investigate into the possible relationship between perchlorate exposure and other health disruptions. Liu et al [136] suggested linking the increased risk of type 2 diabetes with increased exposure to perchlorate and other goitrogens. Formed upon data obtained from NHANES 2001-2014, 11,443 people were tested for perchlorate levels and then obtained data were correlated with prevalence of diabetes in studied group.…”
Section: Other Potential Perchlorate Exposure Health Riskmentioning
confidence: 99%
“…Over the last 10 years, numerous studies also describe other possible perchlorate side effects than just thyroid effects. There are also works on the risk of diabetes, thyroid cancer, changes in blood morphology, parathyroid disorder or even hearing disorders [135][136][137][138][139][140]. The latter are less frequent than those focusing on disruptions of thyroid hormone levels, which are often missed out in various studies.…”
Section: Other Potential Perchlorate Exposure Health Riskmentioning
confidence: 99%
“…Hence, further validation studies with species and portionsize considered are needed. Fourth, low levels of thiocyanate could also be found in milk and cassava (10,51,52), hence, urinary thiocyanate is not perfectly specific for CVs in this non-smoking population. However, the inverse associations were not significantly altered by adjusting the total dairy adequacy component.…”
Section: Discussionmentioning
confidence: 86%
“…Demographic, socioeconomic, lifestyle, and dietary information was collected with questionnaires by trained interviewers. Race/ethnicity was categorized as non-Hispanic white, non-Hispanic black, Mexican American, and others ( 10 , 18 ). Family poverty income ratio (PIR), a measure of family income, was classified into three categories (<1.3, 1.3- < 3.5, ≥ 3.5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation